Re-imagining the Role of Postgraduate Research towards a Research-Intensive University in Namibia - Rachel Ndinelao Shanyanana-Amaambo; Anna Niitembu Hako (European Scientific Journal, ESJ, 2025)
This paper explores the role of postgraduate research in contributing to and achieving a research-intensive university in Namibia, focusing on innovation and national development. Globally, research is widely recognized as a key driver of innovation and development, and universities play a crucial role in exposing students to research processes while researchers carry out research to address national challenges. However, to achieve innovation and contribute to national developmental goals, state funding is crucial for research activities in universities. According to Namibia's Vision 2030, which outlines a goal of becoming an industrialized society with healthy, empowered, innovative, confident, and determined citizens, research is seen as a key factor in driving national progress. The Ministry of Higher Education has developed policies to enable strong research and innovation systems, while universities have adopted policies to promote research for innovation and development. Despite these policies and endeavors, University of Namibia (UNAM) is ranked 16th out of the top 100 universities in Africa and falls short in international research and publication rankings. Therefore, this paper aims to address the following objectives: (a) to understand UNAM’s strategies for promoting research for innovation and national development, (b) to conceptualize research-intensive universities, (c) to analyze UNAM’s research policies and funding opportunities, and (d) to assess the role of postgraduate research in achieving a research-intensive university in Namibia. This conceptual paper's main goal is to investigate UNAM’s ideas on postgraduate research's role in becoming a research-intensive institution and its benefits to creativity and economic growth. This approach enables a discourse that can lead to a potential research framework that may assist UNAM’s efforts to establish a research-intensive university environment, to contribute towards the realisation of Namibia’s National Development Goals.